PELATIHAN MEDIA SOSIAL SEBAGAI MEDIA PROMOSI DESA WISATA DI DESA NGARGOREJO, KECAMATAN NGEMPLAK, KABUPATEN BOYOLALI - Setyo Purwanto; Diana Sukorina; Aurora Luna Marsela; Abdullah Zailani (Surakarta Abdimas Journal, 2025)
This community service program aims to enhance digital literacy among the residents of Ngargorejo Village, Ngemplak Subdistrict, Boyolali Regency, by providing training on social media as a tool for promoting the village’s tourism potential. Ngargorejo Village possesses significant tourism potential, including natural beauty, local culture, and distinctive products. However, the community's limited knowledge of social media utilization poses a major challenge in effectively promoting these assets. The training program was designed using a participatory workshop approach, involving ten participants from local tourism managers and small business owners (UMKM). The training materials covered the creation of social media accounts, content development, management strategies, and hands-on practice. Evaluation results indicate a significant improvement in participants’ understanding of social media, with the average pre-test score of 49 increasing to 85 in the post-test. Additionally, the quality of participants uploaded content showed notable improvements in terms of visualization, narrative, and consistency. However, challenges remained, including low initial digital literacy, limited internet infrastructure, and inconsistency in content management after the training. To address these issues, the program provided solutions such as individualized mentoring, structured content guidelines, and the establishment of a village social media management team. This program has successfully provided the community with relevant digital skills, enabling them to independently promote their village’s potential. Recommendations for program sustainability include advanced training, infrastructure improvements, and local government support for regular content management.